A comprehensive survey on the present scenario and future production potentials of small-scale turkey farming in Bangladesh - Hossain, MA; Dey, B; Lahiry, A; Ahmed, T; Akter, M; Ferdows, J; Das, SC (Bangladesh Journal of Animal Science, 2024)
Turkey (Meleagris gallopavo) is one of the potential species of specialized fowls, quite popular in western countries, has recently been introduced in Bangladesh, and gained considerable attention from small-scale poultry farmers. The purpose of this study was to assess the current scenario, production systems and potentialities of turkey farming in Bangladesh. Data were collected using a pre-tested questionnaire from 100 turkey farmers residing in rural areas in different districts of Bangladesh. The problems and prospects of turkey rearing in the selected areas were quantified and assessed. No illiterate farmers were involved in turkey farming and 97% of the farmers have small household with 3.67 members per family. Most of the farmers (60%) were medium income size with income range BDT 250001 to 400000 year. Most of the farmers (57%) reared turkey for meat purpose whereas the average turkey population per household was 43.20 birds. About 24% of farmers reared turkey in confinement system, and 76% of farmers reared in semi-intensive management system and 68% of farmers had no related training on turkey farming. All farmers use ready broiler/layer feed due to the unavailability of turkey feed that was bought from local market. Grazing was practiced to supply vegetative plants as diet for turkeys. Most of the farmers (86%) vaccinate turkey regularly, and among them 96% complained about vaccine unavailability. Average mortality was recorded at around 6.2%. All the farmers follow a natural breeding system for reproduction. The farmers mentioned that turkey farming is decreasing day by day due to unskilled farmers, lack of turkey ready feed, unavailability of vaccines and lack of marketing facilities. Collectively, it can be inferred that the introduction of ready-made turkey feed, ensuring vaccination, providing financial and technical assistance and offering training to small-scale turkey farmers are the pivotal factors in boosting small-scale turkey farming in Bangladesh. This, in turn, may have the potential to increase household income and generate employment opportunities for youth, rural women, and small-scale marginal farmers. Bangladesh Journal of Animal Science 53 (2): 40-54, 2024